O Impacto da governança de TI na prestação de serviços para as empresas - Brígido, Marcelo Carneiro (2015)
The Information Technology sector is no longer a mere support of industry and now has great strategic importance in enterprises. Currently, in the information age, it is essential to join the IT governance mechanisms to ensure a safe technological environment, reliable, transparent and providing services with excellence. In this context, this study has the general objective to evaluate the perception of internal managers and IT staff on the impact of IT governance mechanisms related to processes in the provision of IT services. Therefore, there will be a single case study, supported by theoretical assumptions about governance and the provision of IT services and shall take place three different data collection methods: survey research, semi-structured interviews, and document analysis. The questionnaire from the survey research was used to identify the degree of adherence of IT governance mechanisms related to processes that are targeted based on best practices of IT services and control. The analysis of documents was performed to verify the evolution of IT processes before and after the implementation of IT governance mechanisms through performance indicators analysis. After these steps were compared the perception of respondents with the analysis of the indicators. The data collected through the questionnaire were analyzed descriptively and the interviews responses were subjected to content analysis. The results showed that the adoption of IT governance mechanisms related to processes improve the provision of IT services, mainly due to the adoption of key IT processes, use of performance indicators, and the adoption of goals. It was identified too that as the adoption of mechanisms matures, there are more benefits delivered, and the satisfaction of stakeholders increase. The mostly of IT governance mechanisms analyzed had positive change over time, so the more effective these mechanisms are better is the performance of IT services.